Targeting fibroblast activation protein in rheumatoid arthritis: from molecular imaging to precision therapeutics - Huang, Yupeng; Wu, Yang; Liu, Huan; Chen, Yuehong; Xie, Qibing; Yin, Geng (Frontiers in Immunology, 2025)
Rheumatoid arthritis (RA), a chronic inflammatory disorder characterized by synovitis and joint destruction, remains a global health challenge. Activated fibroblast-like synoviocytes (FLS), which play a crucial role in the progression of RA, demonstrate tumor-like invasiveness and secrete inflammatory mediators. Fibroblast activation protein (FAP), a type II transmembrane serine protease, has been extensively studied in oncology for decades and has yielded significant clinical benefits. FAP is highly expressed in tumor-associated fibroblasts and plays a pivotal role in tumor growth, dissemination, and immune escape. In cancer imaging, small-molecule FAP inhibitor (FAPI) PET/CT has demonstrated superior sensitivity for detecting primary tumors and metastases. Additionally, FAP-targeted radionuclide therapy has emerged as a promising strategy for delivering precise radiation to tumors, while sparing healthy tissues. Beyond oncology, research on FAP in non-malignant diseases is rapidly advancing. In RA, FAP is overexpressed in RA-FLS but scarce in normal tissues. Thus, FAPI PET/CT can accurately visualize synovitis and monitor the treatment response in patients with RA. Similarly, FAP imaging is used to assess extra-articular manifestations, such as interstitial lung disease and cardiac fibrosis, by mapping fibroblast activity, offering a non-invasive tool. Moreover, emerging therapies, such as FAP-targeted photodynamic therapy, selectively eliminate pathogenic cells in RA models, highlighting their therapeutic potential. This review highlights the advances in FAP-targeted imaging for RA, specifically focusing on FAP as a key biomarker for diagnosis, disease evaluation, and potential therapeutic use in RA.